2001
DOI: 10.1159/000048844
|View full text |Cite
|
Sign up to set email alerts
|

Limited Heat-Shock Protein 72 Induction in Caco-2 Cells by <i>L</i>-Glutamine

Abstract: Background/Aims:L-Glutamine (L-gln) is a conditionally essential amino acid which is consumed by certain tissues like the intestine in large amounts as energy source during critical illness. Apart from nutritive action, recent data suggest a link to heat-shock protein (hsp) induction. We investigated the effect of L-gln on hsp72 expression in the intestinal cell line Caco-2 under basal and heat-shock conditions and compared it with related amino acids. Methods: Total cellular protein was extracted and separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…administration of glutamine by a single dose of 0.75 g/kg. Ex vivo studies [16][17][18] showed that glutamine at a plasma concentration of 4-8 mmol/L could promote HSP expression best. In the studies of Wischmeyer et al, 2 Uehara et al 15 and Singleton et al, 5 where they used i.v.…”
Section: Discussionmentioning
confidence: 99%
“…administration of glutamine by a single dose of 0.75 g/kg. Ex vivo studies [16][17][18] showed that glutamine at a plasma concentration of 4-8 mmol/L could promote HSP expression best. In the studies of Wischmeyer et al, 2 Uehara et al 15 and Singleton et al, 5 where they used i.v.…”
Section: Discussionmentioning
confidence: 99%
“…It is fully broken down to free L-GLN in G15 min following administration (32). The alanyl-glutamine dipeptide was chosen, as alanine is not known to lead to significant enhancement of HSP-70 ( (33) and Wischmeyer PE, unpublished observations). Further, we found that alanine alone was not protective against lethal endotoxemia (Wischmeyer PE, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…IAP distribution along the small intestine is opposite between pigs and rodents, the former having higher IAP activity in the ileum and lower in the duodenum compared with rodents (126,144) . Human cell line Caco2 and porcine IPEC-I display inducible HSP (for example, HSP70) (145,146) . Human cell line Caco2 and porcine IPEC-I display inducible HSP (for example, HSP70) (145,146) .…”
Section: Differences Between Pigs and Humans Or Pig Studies With No mentioning
confidence: 99%